(untitled) (Scientific journal of the Fergana State University, 2024)
In the speech of modern Uzbek and Russian novels, the article reflects on the question of the ironic understanding, expression of the existence of writers. In order to prove the scientific-theoretical views presented, examples from the novels “balance” by Uzbek writer Ulugbek Hamdam and “Sarob” (“Miraj”) by Russian writer Georgy Pryakhin were subjected to analysis on a comparative basis. The relevance and necessity of the problem posed in the introduction to the article is based. And in the Department of literature analysis and methodology, scientists who conducted scientific research on the problem were Gegel, G.N.Pospelov, E.V.The scientific and theoretical views of such scientists as khalizev determined the exact methodological support of the study. As part of the results and analysis, however, scientific results about the relationship of theoretical views on irony with the object of study, and to prove advanced scientific-theoretical ideas, fragments from the novel of writers were drawn into the analysis. At the end of the article, the conclusions presented as the result of the research are listed, a list of the literature used is given.